1990
DOI: 10.1103/physrevb.42.5221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interdiffusion on the electronic properties of HgTe-CdTe superlattices

Abstract: The growth of Hg Te-CdTe superlattices has shown the importance of the interdiffusion of constituent atoms across the interfaces of heterostructures. We study the effect of these processes on the electronic properties of these superlattices in the semiconducting regime using a multiband envelope-function approach. The influence of the strain resulting from the lattice mismatch for HgTe-CdTe superlattice growth on CdTe substrates is found to weakly modify the light-hole subbands while heavy-hole levels are lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[12][13][14][15] Ram-Mohan et al 13 employed the envelope function method and developed a transfer-matrix procedure to calculate the superlattice states. They accounted for the full 8 ϫ 8 Kane Hamiltonian including all second-order terms representing the far-band contributions, but did not apply their results to a calculation of the optical constants.…”
Section: Experimental and Theoretical Detailsmentioning
confidence: 99%
“…[12][13][14][15] Ram-Mohan et al 13 employed the envelope function method and developed a transfer-matrix procedure to calculate the superlattice states. They accounted for the full 8 ϫ 8 Kane Hamiltonian including all second-order terms representing the far-band contributions, but did not apply their results to a calculation of the optical constants.…”
Section: Experimental and Theoretical Detailsmentioning
confidence: 99%
“…7 Interdiffusion was found to occur in the HgTe/CdTe SLs grown at temperatures above 180 C, 51,52 which would enhance the band gap at the interface relative to the abrupt HgTe/CdTe SLs. 13,49 Theoretical analysis of AlAs/GaAs SLs also suggested that chemical intermixing across the interface shifted significantly the SL energy levels. 15 Simulation of InAs/GaSb SLs indicated distinct energy levels for the interfaces due to different interfacial bonding and chemical intermixing.…”
Section: Resultsmentioning
confidence: 99%
“…10 Further theoretical efforts have also been focused on the contribution of disorder and interfacial localization in the inverted QWs. 11,12 Unfortunately, the growth of the SL and accurate control of the layer thickness are of particular tricky, and the quality of the SL is inevitably affected by the interfacial effects of, e.g., chemical interdiffusion 13 and layer thickness fluctuation. 14,15 Among numerous optical studies of HgTe/CdTe SLs was photoluminescence (PL) very active, by which the thickness fluctuation, 14 valenceband structure, [16][17][18] and minibands 7 were investigated separately.…”
Section: Introductionmentioning
confidence: 99%